Study on the incremental carbon sink of tea plantations under spatio-temporal variation characteristics - Pan, Yaxiang; Bao, Jingling; Ji, Yuxuan; Li, Wen; Lin, Weiyu; Fan, Shuisheng; Mao, Liyu (Frontiers in Environmental Science, 2025)
Tea plantation ecosystems have an important function as carbon pools. It is of great significance to clarify the spatial and temporal patterns of carbon sinks in tea plantations, and to analyse the driving factors of carbon sinks in tea plantations, in order to understand the characteristics of carbon sinks in tea plantations, and to expand the ways of increasing carbon sinks in tea plantations. In this study, we selected the data of nine prefecture-level cities in Fujian Province, a major province of tea industry, from 2010 to 2022, and borrowed the standard deviation ellipse and trend surface analysis methods to clarify the spatial and temporal evolution of the carbon sinks in tea plantations, and combined with the geodetic detector model to explore the driving factors of spatial differentiation. The results show that: (1) During the period of 2010–2022, the total carbon sink of tea plantations in Fujian Province increased by 133.12 × 105Mg, showing a continuous growth trend; in terms of spatial distribution, the intensity of tea plantation carbon sinks in the study area showed a gradual and present trend of migration and concentration from the southwest to the northeast. (2) Construct the evaluation index system of carbon sinks in tea plantations, divided into social, living, industrial and population factors and other four categories of eight indicators. (3)The single-factor driver of tea plantation carbon sinks shows that it is mainly affected by industrial scale, population density and industrial structure, with q-values exceeding 0.5. (4)The interaction of the drivers shows that the urban-rural disparity and industrial scale have the highest interaction effect, with q-values reaching 0.9698. The study provides decision-making assistance for expanding the ways of increasing the amount of carbon sinks in tea plantations from the perspectives of clarifying the influence on spatial and temporal heterogeneity of tea plantations’ carbon sinks and revealing the driving factors.